Encephalitis with reversible splenial and deep cerebral white matter lesions associated with Epstein–Barr virus infection in adults - Guo YJ (Dove Medical Press, 2017)
Yanjun Guo,1 Shuhui Wang,1 Bin Jiang,1 Jianle Li,1 Lei Liu,2 Jiawei Wang,2 Weiqin Zhao,1 Jianping Jia1 1Department of Neurology, Beijing Friendship Hospital, Capital Medical University. Beijing, China; 2Department of Neurology, Beijing Tongren Hospital, Capital Medical University, Beijing, China Background: Approximately 200 cases of mild encephalitis with reversible splenial (MERS) and deep cerebral white matter lesions have been reported since MERS was first defined in 2004. MERS occurs more frequently in children; in adults, only ~60 cases have been reported. Until now, only four cases of MERS in adults have been associated with Epstein–Barr virus (EBV). Case presentation: We report three adult cases of MERS associated with EBV infection in China. For all three patients, cranial magnetic resonance imaging (MRI) indicated solitary reversible splenial and/or perilateral ventricle white matter lesions with reduced diffusion. In the present report, all patients were adults presenting with high fever, headache, apathy, and confusion, as well as significant signs of meningeal inflammation. These symptoms peaked 10–14 days after disease onset, with serious hyponatremia (112–129 mmol/L), an elevated cerebrospinal fluid white blood cell count (80–380/mm3), and significantly increased protein levels (1,010–1,650 mg/dL). Cranial MRI indicated abnormal signal intensity in the splenium of corpus callosum and symmetrically reversible lesions scattered in the thalamus and deep cerebral white matter. The clinical symptoms tended to improve after ~10–14 days of antiviral treatment. However, these patients recovered more slowly than patients with viral meningitis. Conclusion: MERS associated with EBV infection in adults occurs less frequently but with more severe symptoms than in children. EBV infection should be considered for patients with MERS symptoms. MERS has a good prognosis. Keywords: mild encephalitis with reversible splenial lesions, Epstein-Barr virus, apathy, hyponatremia, corpus fluid